Media, Structures, and Power - EDWARD A. COMOR (University of Toronto Press, 2011)
Given the fact that Robert Babe’s scholarship is ongoing, the reader might well ask the question, ‘Why publish this collection now?’ In response, let us place his work in three contexts: its influence on both policymaking and the academy; its timeliness in light of contemporary economic and cultural developments; and, finally, its place as a reflection and representation of Canada’s uniquely historical, holistic, and dialectical approach to both social science and societal concerns. For many years, Babe’s contributions to political economy, telecommunications policy, ecological studies, and media theory have been widely recognized. The status and accomplishments of this volume’s contributors itself underlines the extraordinary range and influence of his scholarship. Indeed, this collection’s publication reflects Babe’s standing in the academy and, more importantly, it presents, for the first time, his otherwise disparate writings as a coherent, developing body of work. In historical terms, the timeliness of this collection is underlined by the contemporary collapse of neoliberalism and what, at this juncture, appears to be the beginning of an important shift in both economic thinking and public policy. As of 2011, decades of pro–free market regulations have intensified contradictions long recognized by Babe: unsustainable here-and-now cultural practices that have emerged alongside mass indebtedness and environmental decay. Thus, in the context of the contemporary crisis, this review of Babe’s varied critical assessments coincides with efforts by political leaders, academics, and activists to construct new ways of organizing social-economic relations. Babe’s work illuminates both past mistakes and future opportunities. In this regard, this collection is prescient